Overview of rabies post-exposure prophylaxis access, procurement and distribution in selected countries in Asia and Africa, 2017–2018 - Sreenivasan, N.; Li, A.; Shiferaw, M.; Tran, C.H.; Wallace, R.; Blanton, J.; Knopf, L.; Abela-Ridder, B.; Hyde, T.; Siddiqi, U.R.; Tahmina, S.; Penjor, K.; et al. (Vaccine, 2019)
Rabies is a neglected zoonotic disease with a global burden of approximately 59,000 human deaths a year. Once clinical symptoms appear, rabies is almost invariably fatal; however, with timely and appropriate post-exposure prophylaxis (PEP) consisting of wound washing, vaccine, and in some cases rabies immunoglobulin (RIG), the disease is almost entirely preventable. Access to PEP is limited in many countries, and when available, is often very expensive. We distributed a standardized assessment tool electronically to a convenience sample of 25 low- and middle-income countries in Asia and Africa to collect information on rabies PEP procurement, forecasting, distribution, monitoring and reporting. Information was collected from national rabies focal points, focal points at the World Health Organization (WHO) country offices, and others involved in procurement, logistics and distribution of PEP. Because RIG was limited in availability or unavailable in many countries, the assessment focused on vaccine. Data were collected between January 2017 and May 2018. We received responses from key informants in 23 countries: 11 countries in Asia and 12 countries in Africa. In 9 of 23 (39%) countries, rabies vaccine was provided for free in the public sector and was consistently available. In 10 (43%) countries, all or some patients were required to pay for the vaccine in the public sector, with the cost of a single dose ranging from US$ 6.60 to US$ 20/dose. The primary reason for the high cost of the vaccine for patients was a lack of funding at the central level to subsidize vaccine costs. In the remaining 4 (17%) countries, vaccine was provided for free but was often unavailable so patients were required to purchase it instead. The majority of countries used the intramuscular route for vaccine administration and only 5 countries exclusively used the dose-sparing intradermal (ID) route. Half (11/22; 50%) of all countries assessed had a standardized distribution system for PEP, separate from the systems used for routine childhood vaccines, and almost half used separate storage facilities at both central and health facility levels. Approximately half (9/22; 41%) of all countries assessed reported having regular weekly, monthly or quarterly reporting on rabies vaccination. While all countries in our assessment had rabies vaccines available in the public sector to some extent, barriers to access include the high cost of the vaccine to the government as well as to patients. Countries should be encouraged to use ID administration as this would provide access to rabies vaccine for many more people with the same number of vaccine vials. In addition, standardized monitoring and reporting of vaccine utilization should be encouraged, in order to improve data on PEP needs.